2000
DOI: 10.1109/41.873218
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investigation of diagnostic media for induction motors: a case of rotor cage faults

Abstract: Results of a comparative experimental investigation of various media for noninvasive diagnosis of rotor faults in induction motors are presented. Stator voltages and currents in an induction motor were measured, recorded, and employed for computation of the partial and total input powers and of the estimated torque. Waveforms of the current, partial powers and , total power, and estimated torque were subsequently analyzed using the Fast Fourier Transform. Several rotor cage faults of increasing severity were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(36 citation statements)
references
References 12 publications
0
28
0
8
Order By: Relevance
“…When a fault exists inside the motor some of frequency components magnitudes are increased with respect to the fundamental component depending on fault type and severity. Thus, by identifying frequencies and magnitudes of these components with respect to fundamental component, both fault type and severity can be addressed [6,7]. This technique is simple and requires …”
Section: A Fault Detection Using Stator Phase Current Signaturementioning
confidence: 99%
See 2 more Smart Citations
“…When a fault exists inside the motor some of frequency components magnitudes are increased with respect to the fundamental component depending on fault type and severity. Thus, by identifying frequencies and magnitudes of these components with respect to fundamental component, both fault type and severity can be addressed [6,7]. This technique is simple and requires …”
Section: A Fault Detection Using Stator Phase Current Signaturementioning
confidence: 99%
“…It is found that the use of partial power signatures gives more information about faults than the use of stator current signatures [6]. This can be achieved by applying the FFT algorithm on the instantaneous partial power signals.…”
Section: Fault Detection Using Partial Power Signaturementioning
confidence: 99%
See 1 more Smart Citation
“…Más concretamente, en [12] se demuestra que, así como una rotura de barra introduce en la corriente principalmente los…”
Section: 23-soluciones Y Otras Técnicas De Diagnóstico En Régimenunclassified
“…En la Fig. 2.6 (reproducciones de las figuras 3, 5, 6 y 7 de [12]), se muestran los espectros de la corriente estatórica del motor de inducción a diagnosticar (superior izquierda), la potencia instantánea de fase (superior derecha), la potencia instantánea total (inferior izquierda) y el par estimado (inferior derecha). En el espectro de la corriente se observan los dos SH, muy cerca del FC, de tal forma que si por ejemplo baja el nivel de carga, pueden verse fácilmente enmascarados por el FC.…”
Section: 23-soluciones Y Otras Técnicas De Diagnóstico En Régimenunclassified